Toothpick use among Epigravettian Humans from Grotta Paglicci (Italy). (1st November 2014) - Ricci, S.; Capecchi, G.; Boschin, F.; Arrighi, S.; Ronchitelli, A.; Condemi, S.
Abstract: This paper deals with two teeth (an upper right M1 and an upper right dM2) from the Epigravettian found in the site of Paglicci (Southern Italy) showing interproximal grooves that are situated below the crown, on the root walls just apical to the cementum–enamel junction. These grooves have been examined on a digital microscope which displays 3D images of the analysed surfaces. The images obtained made it possible to interpret these interproximal grooves as tooth picking activities that can be interpreted as an attempt to alleviate sore gums. The comparison with experimental images from available literature made it possible to form hypotheses concerning the nature of the probes that might have been used by the humans. Copyright © 2014 John Wiley & Sons, Ltd.